PENGARUH PERILAKU KEWIRAUSAHAAN TERHADAP KINERJA USAHA TOKO IMELDA PONSEL KOTA TELUKDALAM KABUPATEN NIAS SELATAN - Hertika Gulo (JURNAL EKONOMI DAN BISNIS NIAS SELATAN, 2022)
This study focuses on two variables of entrepreneurial behavior and business performance. Aims to determine the effect of entrepreneurial behavior on business performance. The method used in this research is quantitative; method of collecting data this is done by distributing questionnaires to 30 customers. The data analysis method used is a simple linear regression analysis method. The results of this study indicate that entrepreneurial behavior has a significant effect on business performance with a t value of 7,638>t table 1,701 and significant level of 0,000<0,5 meaning that the entrepreneural behavior variable influence business performance. Linear regression test results y=15,355+o,674 x. Then the linear regression coefficient for b is 0,674, meaning that for every 1 unit increase in entrepreneurial behavior, business performance will increase by 0,674 units.